Simple hydroponics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The Asian Vegetable Research and Development Center (AVRDC) has developed a simple hydroponic system for growing vegetables, using old clothes and plastic cups as a basis. Old plastic cups are perforated and filled with an absorbent medium such as...